Types of some Mexican names in Amaranthaceae s.l. (Caryophyllales) - Sandoval-Ortega, Manuel Higinio; Zumaya-Mendoza, Silvia (Phytotaxa, 2023)
The family Amaranthaceae has a cosmopolitan distribution and it is one of the most diverse families within the order Caryophyllales. Species of Amaranthaceae live mainly in arid environments, saline habitats, or disturbed areas. Nomenclature is the necessary first-step to study the members of this group, aiming to clarify their identity which is often critical. The types of four names in Amaranthaceae (sensu lato, including Chenopodiaceae)—Chenopodium berlandieri, Celosia monosperma, Iresine grandis var. glabrata, Iresine interrupta—with Mexican loci classici are designated in the present paper, including comments on their identities.